2020
DOI: 10.1111/jtxs.12550
|View full text |Cite
|
Sign up to set email alerts
|

Can we understand food oral processing using Kano model? Case study with confectionery products

Abstract: This study had two objectives, to determine oral processing parameters and its correlation with mechanical properties of selected confectionery products and to categorize oral processing and sensory attributes based on a Kano model. Thirteen panelists analyzed five confectionery products in the oral processing part of the study. In parallel, 327 interviews participated in a field survey to enable analyzing responses to food quality and oral processing attributes. It has been confirmed that oral processing para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Indeed, there are numerous foodstuffs that are easily masticated and liked because of that property. Using the Kano model, Djekic, Ilic, Guiné, and Tomasevic (2020) explained that the young population is also interested in sweets that can be easily masticated. They also found that the products demanding fewer chews are desired, and products that break down easily are attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are numerous foodstuffs that are easily masticated and liked because of that property. Using the Kano model, Djekic, Ilic, Guiné, and Tomasevic (2020) explained that the young population is also interested in sweets that can be easily masticated. They also found that the products demanding fewer chews are desired, and products that break down easily are attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TPA attributes were not related to oral processing parameters in studies of different breads with distinct foam‐like structures, confirming the important role of the structural features of each type of food on the chewing pattern and the intrinsic limitations of TPA in measuring mechanical properties (Gao et al., 2015, 2017; Puerta et al., 2020; Tournier et al., 2014). Recently, empirical methods, such as the Kramer shear test and the Warner‒Bratzler shear test, have been used to measure those mechanical properties of foods that can better reflect their mechanical strength regardless of their geometry (Álvarez et al., 2020; Djekic, Ilic, Guiné, et al., 2020; Djekic, Ilic, Lorenzo, et al., 2020). The maximum shear force has a better correlation with oral processing parameters than does TPA hardness (Djekic, Ilic, Lorenzo, et al., 2020).…”
Section: Effect Of Food Structure On Chewing Patternmentioning
confidence: 99%
“…It is obvious that we need to understand consumer preferences associated with taste and textural characteristics of cereal-based products, such as wafers or biscuits, and better characterize phenomena occurring in the products, to enable successful development of these products. One of the latest researches used a Kano model to understand food oral processing of confectionery products [111], starting from a field survey on consumer preferences towards oral processing.…”
Section: Modelling Properties Of Cereal Products and Characteristics Of Consumptionmentioning
confidence: 99%